Unmasking the Diagnosis of Acromegaly - Paewponsong J. (2023)
The diagnosis of acromegaly is still a difficult task, as the disease has a slow onset and progression, and some of its symptoms may resemble those of other common conditions. Delays in diagnosis are common. Moreover, due to the continuous requirement for mask-wearing in many healthcare settings to prevent the spread of COVID-19, it is crucial to conduct a comprehensive examination of each patient without a face mask.